PELATIHAN PEMBUATAN PROPOSAL KEGIATAN PADAREMAJADUSUNNGEPUH LOR, DESA BANYUSIDI, PAKIS, MAGELANG,JAWA TENGAH - Muhammad Hasyim (Asian Journal of Innovation and Entrepreneurship, 2014)
Dusun Ngepuh Lor is one of the Dusun in the Magelang region that has KarangTaruna as a youth organization Dusun level. As an organization certainly needs theability of its members to manage, create activities and to develop themselves. One of thesupporting capabilities in the organization is to make a proposal. Making the proposal isone of the capabilities necessary to advance the organization's activities. By having thecapability and ability in making the proposal, the youth will be easier to find funding tosupport its organization. Given these training activities, the youth can enrich theknowledge and capabilities regarding computer usage and making proposals.